Tourism management : an introduction - Page, Stephen, 1963- (Oxford ; Burlington, MA : Butterworth-Heinemann, 2011)
'Tourism Management' is a complete synthesis of tourism, from its beginnings, through to the major impacts it has on today's global community, the environment and economy.
Previous editions had subtitle: Manageing for change.
Previous edition: 2009.
Includes bibliographical references and index.
Keywords: Tourism -- Textbooks; Tourism -- Management -- Textbooks